GENDER-RELATED CORRELATION BETWEEN COMPUTED TOMOGRAPHY VERTICAL SIZE OF THE LUMBAR SPINE ANATOMICAL STRUCTURES AND ANTHROPO-SOMATOTYPOLOGICAL PARAMETERS IN ADOLESCENTS - Majewski, O.Ye.; Pinchuk, S.V.; Ivanytsya, A.O. (World of Medicine and Biology, 2015)
When analyzing sexual differences correlations computed tomography sizes of the lumbar spine on median-sagittal sections with anthropometric, somatotypological parameters and indicators component composition of body weight, found that in girls the number of significant relationships, and their power considerably greater than in boys. In addition, in young men found considerably greater amount significant feedback than in girls. The largest number of reliable connections with anthropo-somatotypological indicators in girls set with height of bodies lumbar vertebrae and the average width of the bodies of the lumbar vertebrae, and in boys – with height of lumbar vertebrae body and height of intervertebral discs between the relevant vertebrae.
Keywords: lumbar spine; computed tomography; anthropometry; healthy young men and women